525 Automated Continuous Instrument Tracking in Laparoscopic Box Trainers Predicts Performance at Assessment: A Prospective Cohort Study in Core Surgical Trainees. (4th May 2021) - Shivank, K; Ilin, R; Walker, K; Brennan, P
Abstract: Introduction: Box-trainers enable deliberate practice of laparoscopic skills and can be equipped with instrument tracking metrics to provide feedback. However, the relationship between metrics, assessment outcomes and practice are unclear. Method: Core surgical trainees were provided take-home box trainers with SurgTrac™ instrument tracking metrics for practice (eoSurgical Ltd., Scotland, UK). Practice was incentivised by certification and video assessment of a basic task, peg capping. Assessment was by consultant general surgeons, using objective structured assessment of technical skills (OSATS). The following metrics were analysed: task duration, distance moved by instruments, average instrument speed, average instrument acceleration, left- or right-handedness and instrument smoothness. Metrics were correlated to OSATS scores using regression analysis. Threshold for significance was p = 0.05. Results: During the study period, there were 1639 peg capping performances by 85 trainees; 103 video recordings were submitted for assessment. All metrics were significantly associated with OSATS score, except instrument acceleration. The multiple linear regression model was highly correlated with actual scores (Pearson correlation 0.658; p < 0.001). Practice was positively correlated with regression model predicted OSATS score (regression analysis; ANOVA p < 0.001). Conclusions: Instrument tracking metrics reliably predict OSATS performance and practice improves predicted score. Trainees can use metrics in unsupervised practice and gauge whether they are improving as expected.